FACTORS INFLUENCING THE PRODUCTION OF PAD RICE (Oryza sativa L.) IN ARAH TIGA VILLAGE, LUBUK PINANG DISTRICT, MUKOMUKO DISTRICT - Murnita Murnita; Herda Gusvita; Dedef sefrianti (Journal of Scientech Research and Development, 2023)
This study aims to analyze what factors affect rice production in the Three-Attire Village of the Mukomuko District Pinang Powder. This study was conducted in June – July 2022. This research method is quantitative descriptive research. The population in this study was all rice farmers with a population of 374 farmers with a sample of 193 people. The data analyzer used is multiple linear regression with the Cobb-Douglas function. The results showed that the factors of production were land area, number of seeds, fertilizer costs, pesticide costs, labor costs, farmer's age, education level, farming experience, and the number of dependents of the head of the family together significantly influences the amount of rice production, while the partial effect is significant, the number of seeds, the cost of pesticides, and labor wages, while the area of land, fertilizer costs, farmer age, education level, farming experience, and the number of dependents on the head of the family has no effect on the amount of rice production. The suggestions in this study are the existence of policies by the government and related institutions in carrying out agricultural development, specifically paddy rice.